The Perception of Product Placement in The Food Products Market: Empirical Research Involving Generation Y In Lublin, Poland - Wioletta WRÓBLEWSKA; Sebastian BIAŁOSKURSKI (Communications of International Proceedings, 2022)
As effective communication is becoming an important element in the operations of companies, entities are adding new forms of promoting products and services to their marketing strategies, with product placement being one of  these. Product placement is aimed at attracting larger audiences, compared to traditional marketing tools, also those using social media. Generation Y (the digital generation), strongly associated with social media, forms an important group for marketers. This research was conducted to analyse the opinions of representatives of younger Generation Y regarding their perception of product placement as a form of advertising in the food products market. In addition, the aim was to measure the marketing outcomes of product placement strategies based on visibility and increased product interest, understood as the purchase of products advertised through product placement. The research involved a group of 276 representatives of younger Generation Y in Lublin. Selected descriptive statistics were used in the analyses (the sum of scores for each issue and their structure, the mean value of the sum of scores (), and to compare the impact of gender on the studied phenomena, the Persona and Sperman rank correlation coefficient were used. The obtained results revealed that product placement is most often spotted in films and TV series as well as on YouTube channels. The products most frequently listed as belonging the product placement category were food products, and in the group of food products, the respondents mainly noticed sweets, soft drinks and snacks. The most frequently spotted types of product placement in the food products market included brand placement, corporate placement and organisation placement. Influenced by product placement advertising in the food products market, the respondents were most inclined to purchase snacks and sweets. The greatest interest, reflected in the number of purchase decisions made under the influence of product placement, was observed for dairy products, soft drinks, sweets and snacks. The respondents’ opinions on product placement were rather neutral; they mainly emphasised that this is a less intrusive form of advertising compared to standard forms, but it limits the opportunity of fully presenting the product. The research topic and the obtained results can be used to develop product placement strategies which, through the use of well-matched techniques, could influence food purchase decisions, inter alia, in the context of reducing the consumption of unhealthy products and promoting healthy food choices.
Keywords: product placement; custom advertising; food market; generation Y